Adapting Restorative Urban Design, for Open Spaces Towards, Thermal Heat Island, Reaching Human Mental Health and Well-being, Case study: Qaitbay Citadel Plaza, Alexandria, Egypt (Future Cities and Environment, 2025)
Nowadays rapidly evolving urban landscape. These challenges increasingly impact residents' mental health and well-being. Overcrowding, noise and air pollution, long commutes, the size of the built environment, landscape and green areas, and the variety of ground surface materials affect outdoor thermal comfort in hot climates to reach mental health and well-being. These public spaces are dealing with the issue of an expanding urban heat island, which affects how users behave. This paper aims to support restorative urban design in Alexandria, Egypt, to reach users thermal comfort, mental health and well-being at the forefront of public spaces. To attain human mental health and well-being in public spaces. Several studies have been done. Such as: Bowling Questionnaire methodology on about 92 participants to assess user perceptions of Qaitbay citadel plaza according to Gehl’s theory. And simulated scenarios to measure material effect on users’ thermal comfort in the plaza using ENVI-met 4.0 program. As the questionnaire found that: 30% rated accessibility as "poor," and only 75% felt almost unsafe in the area. Thermal discomfort was prevalent, with 40% reporting the temperature as "uncomfortable," 63% finding shaded areas inadequate, and 75% attributing discomfort to heat-retaining surface materials. And mitigate urban heat island phenomena. Through the use of different paving material mitigation strategies, green spaces, and the landscape through different scenarios, till reaching the best scenario which decrease the minimum temperature 2.06 °C and the maximum temperature 3.59 °C for users’ thermal comfort and wellbeing inside the space reaching to a restorative urban public space.